Relationship of Main Pulmonary Artery (Truncus Pulmonalis) Diameter With Hospital Stay and Mortality in Pulmonary Hypertension Patients Admitted to the Emergency Department - Goktekin, Mehmet Cagri; Aksu, Feyza; Perilioglu, Ahmet Zafer; Akkoc, Ramazan Fazil (Springernature, 2023)
Introduction: Pulmonary hypertension (PH) is a haemodynamic and pathophysiological disease significantly associated with morbidity and mortality. The increase in pulmonary vascular resistance, high pulmonary artery pressure and wall tension that occurs in PH results in dilatation of the main pulmonary artery (truncus pulmonalis), one of the largest and most important vessels in the body. The aim of this study is to investigate the relationship between the diameter of the truncus pulmonalis and hospitalization, length of hospital stay, and mortality in patients diagnosed with PH.Methods: Demographic characteristics, number of Emergency Department (ED) admissions, post-admission status, treatment, truncus pulmonalis diameter, and mortality were evaluated statistically through the patient files of 115 PH patients who presented to the ED of Firat University Faculty of Medicine, Elazig, Turkiye, between January 2022 and December 2022.Results: Of the 115 PH patients who came to the ED, 70 (60.8%) were women and 45 (39.2%) were men, with a mean age of 78.77 +/- 8.72 years. Fifty-one of these patients were discharged from the ED after treatment, and 64 were hospitalized. The mean length of hospital stay was two (min=0, max=38) days. Thoracic CT scans demonstrated that the mean diameter of the truncus pulmonalis of the patients was 34.874 +/- 3.288 mm (35.20 +/- 3.6509 mm in women, 34.367 +/- 2.5836 mm in men; p=0.351) and there was no statistically significant relationship with mortality (p=0.496), hospitalization (p=0.806), and length of hospital stay (p=0.416). There was a statistically significant relationship between mortality rate and male gender (p=0.02) and comorbidity (p=0.001).Conclusion: It was determined that there was no statistically significant relationship between the truncus pulmonalis diameter and gender, comorbidity, hospitalization, length of hospital stay, and mortality in this study in which single-centre one-year admissions of PH, which differ in aetiology, epidemiology, and demographic features were examined. However, among the patient demographics, a significant relationship was determined between gender and the number of comorbidities and mortality.
Keywords: Categories; Family/General Practice; Anatomy; Emergency large blood vessels; mortality; emergency department; pulmonary hypertension; main pulmonary artery (truncus pulmonalis) diameter